Thin film electroluminescent indicators for on-board systems of GTR-mapping information - Ленков, С. В.; Зубарев, В. В.; Жеревчук, В. В; Перегудов, А. Н.; Шевченко, Р. А. (Proceedings of National Aviation University (archive), 2000)
The analysis methods for the creation, structure and materials of electroluminescent indicators for the board information display systems. Proposed new indicator material layers to significantly improve brightness and reduce radiation by horn-excitation voltage